2001
DOI: 10.1016/s0309-1740(00)00092-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the carcass composition of yearling bulls of “Asturiana de los Valles” breed from the dissection of a rib joint

Abstract: To evaluate dierent methods of estimating bovine carcass composition, seventy yearling bulls of the``Asturiana de los Valles'' beef breed were slaughtered and their carcass composition estimated by a commercial dissection of the right half-carcass and by tissular dissection of the 6th and 10th rib of the left half-carcass. Correlation and regression analyses were used to identify the most accurate predictors of carcass composition. In simple regression, the percentage of lean in the 10th rib was the most accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
1
11
1
1
Order By: Relevance
“…At the same time the 10th rib was removed, weighed, and stored at 48C for later dissection to yield the corresponding whole SC and IM tissues. The tissue composition around this rib was deemed representative of the tissue composition of the carcass as a whole (Olivá n et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time the 10th rib was removed, weighed, and stored at 48C for later dissection to yield the corresponding whole SC and IM tissues. The tissue composition around this rib was deemed representative of the tissue composition of the carcass as a whole (Olivá n et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The adipose tissue depots used in this study, expressed as a presentage of carcass weight, included 8.4% IT and 2.2% SC fat estimated using 6th rib dissection according to Oliván, Martínez, García, Noval, and Osoro (1999) and 1.7% IM measured using Soxhlet extraction. Wegner, Albrecht, and Ender (1998) also found that the IT depot had the greatest amount of fat which comprised 45% of total carcass fat in 24 months old Black Pied bulls.…”
Section: Adipose Tissuementioning
confidence: 99%
“…In general, comparing adipose tissues, genotype effect was more pronounced in IM and SC FA profiles than in IT, for which no significant differences between genotypes were found in SFA, PUFA (n À 6 and n À 3) and UFA. In addition, the contribution of IT and SC depots to the 6th rib dissection (used as a predictor of carcass composition, Oliván et al, 1999) was dependent on genotype. Double-muscled animals were found to have the lowest IT (4.9% of total rib weight) and SC (1.1% of total rib weight) fat percentages while AM animals had the highest IT (9.8%) and SC (3.2%) fat percentages (P < 0.001).…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…were recorded as bone. The 6th rib dissection was used as a predictor of the carcass composition (Oliván et al, 1999).…”
Section: Carcass Measurements and Samplingmentioning
confidence: 99%